DINAMIKA POLITIK PENDIDIKAN AGAMA DI INDONESIA - Muhammad Bisyri (TARBIYA: Journal of Education in Muslim Society, 2014)
Law No. 4/1950 Jo. Law No. 14/1954 stated that the purpose of education was to create a moral human being.  It was interpreted that moral human being could be created not only through religion because the basis of moral was not always religion.  Therefore, in the 1950s religion was not compulsorily taught at school.  At later stage, as stipulated in Law No. 2/1989 that education was to create a complete human being devoting to God Almighty One, religion was a compulsory at school.  The gap between these laws was that school with certain religion was not required to teach other different religions.  This stipulation has later become problematic.  In 2003, Law No 20 about national education system was enacted emphasizing the existence of religion education.  This law mandated that religion was a compulsory in every education institution whereby the subject matters to be suited to the students and taught by the relevant teacher.  It has been apparent that education has historically been improved from time to time. DOI: 10.15408/tjems.v1i2.1272